Effects of Long-Term Serum Starvation on Autophagy, Metabolism, and Differentiation of Porcine Skeletal Muscle Satellite Cells - Yi Wang; Juan Gao; Bojun Fan; Yuemin Hu; Yuefei Yang; Yajie Wu; Jiaqiao Zhu; Junwei Li; Feng Li; Huiming Ju (Veterinary Sciences)
This study investigated the effects of long-term serum starvation on autophagy, metabolism, and differentiation of porcine skeletal muscle satellite cells (SMSCs) and elucidated the role of autophagy in skeletal muscle development. Our findings provide a theoretical basis for improving meat production in domestic pigs. The SMSCs isolated and preserved in our laboratory were revived and divided into six groups based on the culture medium serum concentration to simulate varying levels of serum starvation: 20% serum (control group), 15% serum (mild serum starvation group), 5% serum (severe serum starvation group), and their autophagy inhibition groups supplemented with 3-methyladenine. After 96 h of culture, the apoptosis rate, mitochondrial membrane potential, reactive oxygen species, and ATP were measured to evaluate the effects of serum starvation on the SMSCs’ metabolism. Additionally, the levels of autophagy-related proteins, autophagosomes, and autolysosomes were measured to investigate the impact of long-term serum starvation on autophagy. The expression of proteins associated with myogenic and adipogenic differentiation (MHC, MyoD1, peroxisome proliferator-activated receptor γ, and lipoprotein lipase) as well as lipid content were also determined to investigate the effects of long-term serum starvation on SMSC differentiation. The results showed that long-term serum starvation induced autophagy through the AMPK/mTOR signaling pathway, accelerated cell metabolism and apoptosis, exacerbated reactive oxygen species accumulation, and inhibited myogenic and adipogenic differentiation of SMSCs. Moreover, these effects were positively correlated with the level of serum starvation. In addition, serum starvation-induced autophagy moderately promoted the myogenic and adipogenic differentiation of SMSCs; however, these effects were insufficient to counteract the inhibition of cell differentiation by long-term serum starvation. This study provides insight into leveraging serum starvation as a stressor to regulate muscle growth and metabolism in domestic pigs.